2001
DOI: 10.4157/grj1984b.74.33
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainable Renovation of the Industrial Complex in Inner Tokyo:

Abstract: Abstract:The most important core that has sustained the innovations of the machinery industry of Japan is the technological complex composed of SMEs in Southern Tokyo, the core of which is Ota-ku. Entering the 1990s, the firms and their industrial complex have changed their respective methods of operations under the drastic change in economic conditions. That is, in addition to the founding (1st) generation the new generation participated as management and engineering staff. This resulted in the crystallizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…One study looking at this was Maruyama (2007), who demonstrated how small-sized manufacturers in Itabashi Ward sought new transaction partners with the aid of their non-transaction social networks. According to Takeuchi and Mori (2001), an effective blend of the traditional skills of machinery-and metal-processing and the locally accumulated electronics technology by new-generation successors in the southern Tokyo area was instrumental in reviving inner-city manufacturing as a national center of the "mechatronics" technology.…”
Section: Manufacturing Activities In the Inner-metropolitan Areasmentioning
confidence: 99%
“…One study looking at this was Maruyama (2007), who demonstrated how small-sized manufacturers in Itabashi Ward sought new transaction partners with the aid of their non-transaction social networks. According to Takeuchi and Mori (2001), an effective blend of the traditional skills of machinery-and metal-processing and the locally accumulated electronics technology by new-generation successors in the southern Tokyo area was instrumental in reviving inner-city manufacturing as a national center of the "mechatronics" technology.…”
Section: Manufacturing Activities In the Inner-metropolitan Areasmentioning
confidence: 99%